Simulation and Analysis of Water-cooled Heat Dissipation of Industrial Silicon Burner based on ANSYS - Sun, Panpan; Hu, Guangzhong; Wang, Ping; Yang, Lei; Luo, Minhong; Yu, Jinghao (International Journal of Mechanical and Electrical Engineering, 2025)
The performance of the water cooling system of a new type of burner plays an important role in the safe and stable operation of the whole equipment. The material properties of steel, such as yield strength and modulus of elasticity, deteriorate under high-temperature conditions, leading to a decrease in the structural load-bearing capacity, which will bring about potential safety hazards when the burner is in operation. In this paper, the coupled thermal-electrical model and fluid temperature field model of graphite electrode and electrode holder of the burner are established, and the water-cooled heat dissipation simulation of the electrode holder of the burner is carried out by taking into account the effects of radiant heat dissipation, air convection, electric current and fluid flow on the temperature of the burner when it is in operation. The simulation results show that: After the inlet flow rate of 42.54L/min liquid water cooling, the temperature of the collet is reduced to the safe temperature, and the wedge-shaped clamping block is below the maximum continuous working temperature of the material, and the temperature continues to decrease with the increase of inlet flow rate. In summary, the minimum inlet flow rate of the water cooling system for the burn-through device is 42.54 L/min.